Visualise the tastes from the label: A study on the taste-colour crossmodal association of crisp and dry - Wang, Mengmeng; Li, Dongning (Frontiers in Psychology, 2022)
Colour is an important guideline for selection and consumption. It also draws attention to the designers, as some modern design styles require them to illustrate the taste of the product with a limited number of colours. In this case, a precise description of the taste-colour association is required. The present study explored the colour-taste crossmodal association of two tastes, crisp and dry, which are normally found in beers and are the preferred flavours of Chinese consumers. Experiments were carried out to determine the characteristics of the colours associated with the two tastes. And the strength of the tastes perceived from the colours with different hue angles was investigated. The results of this study reveal that the hue and chroma can both affect the perception of these tastes. Both tastes can be perceived from the same colour, but the strength of the taste can be varied from different hues.